Blood concentrations of B-type natriuretic peptide and N-terminal prohormone B-type natriuretic peptide as markers of left ventricle diastolic function in patients with chronic renal failure - Petrović, Milica; Grdinić, Aleksandra; Bokonjić, Dubravko; Rabrenović, Violeta; Antić, Svetlana; Terzić, Brankica; Stamenković, Dušica; Stajić, Zoran; Petrović, Dejan; Ignjatović, Ljiljana; Pejović, Janko; Jovanović, Dragan (Vojnosanitetski pregled, 2017)
Background/Aim. Patients with chronic renal failure (CRF) have increased cardiovascular morbidity and mortality. It is unknown which biomarkers best describe the degree of diastolic dysfunction in patients with CRF. The aim of this study was to determine the correlation between B-type natriuretic peptide (BNP), N-terminal prohormone brain natriuretic peptide (NTproBNP) and left ventricular diastolic dysfunction (DD-LV) with the degree of CRF. Methods. The study included 100 adult patients with CRF without major cardiac and cerebral incidents who did not start actively treating CRF. According to the degree of CRF, the patients were divided into two groups: G1 (moderate degree), glomerular filtration rate (GFR) ≥ 30 mL/min/1.73 m2, and G2 (more severe degree), GFR < 30 mL/min/1.73 m2. Blood concentrations of BNP and NTproBNP were measured and Doppler echocardiographic measurement performed to estimate diastolic dysfunction (DD-LV). According to the degree of DD-LV, all the patients were divided into two groups: DD-LV1 (mild diastolic dysfunction) and DD-LV2 (severe diastolic dysfunction). According to the degree of CRF and DD-LV, the patients were divided into four groups: I (G1, DD-LV1), II (G1, DD-LV2), III (G2, DD-LV1) and IV (G2, DD-LV2). Results. There was a highly significant statistical correlation between BNP and NTproBNP with GFR (p < 0.001), and DD-LV with BNP (p < 0.023) and NTproBNP (p = 0.035). In patients with DD-LV2, a statistically significantly higher BNP concentrations were registered in patients with G2 (p < 0.001). Unlike BNP in the patients with diastolic dysfunction DD-LV1 and those with diastolic dysfunction DD-LV2, significantly higher concentrations of NTproBNP were registered in the patients with G2 (DD- LV1: p = 0.006; DD-LV2: p < 0.001). Conclusion. Biomarkers BNP and NTproBNP are not the best predictors in the assessment of diastolic dysfunction because they are correlated with the degree of renal insufficiency.